The chamber - Grisham, John, 1955- (Arrow, 1994)
In the corridors of Chicago's top law firm:Twenty -six-year-old Adam Hall stands on the brink of a brilliant legal career.Now he is risking it all for a death-row killer and an impossible case.Maximum Security Unit, Mississippi State Prison:Sam Cayhall is a former Klansman and unrepentant racist now facing the death penalty for a fatal bombing in 1967.He has run out of chances -- except for one: the young, liberal Chicago lawyer who just happens to be his grandson.While the executioners prepare the gas chamber, while the protesters gather and the TV cameras wait, Adam has only days, hours, minutes to save his client.For between the two men is a chasm of shame, family lies, and secrets -- including the one secret that could save Sam Cayhall's life... or cost Adam his. --back cover